The effects of lower reserve requirements on money market volatility - Lown, Cara S.; Brunner, Allan D. (American Economic Review, 1993)
In late 1990, the Federal Reserve eliminated reserve requirements on nonpersonal time deposits, and required reserves fell by about $10 billion, an almost 20-percent reduction. In early 1992, reserve requirements against transaction accounts were lowered from 12 percent to 10 percent, releasing an additional $3.5 billion of required reserves.1 These reductions, by lowering total reserve balances, potentially could increase reserve market volatility, impeding the implementation of monetary policy and possibly spilling over into other markets. This paper examines the effects of reserve requirements on market volatility and on the central bank's ability to achieve shortrun policy objectives. Although a number of earlier studies have examined the effects of reserve requirements on the effectiveness of monetary policy, our approach differs in two important respects. First, we focus on the ability to achieve short-run objectives. Second, we provide empirical estimates of the likely effects of lower reserve requirements. The central bank cannot directly achieve its long-run objectives of output and price stability, so it uses policy rules to set shortand intermediate-run targets for certain economic variables, such as interest rates or monetary aggregates, consistent with its long-term goals.2 The central bank cannot, however, perfectly control shortor intermediate-run targets, so it also relies on a set of operational rules. Operational rules are used to set instruments (such as reserve requirements, the discount rate, and openmarket operations) in order to achieve the shorter-run targets. Previous studies, such as Ira Kaminow (1977), Jeremy Siegel (1981), Ernst Baltensperger (1982), Richard T. Froyen and Kenneth J. Kopecky (1983), and Brian R. Horrigan (1988), focused exclusively on longer-term objectives of monetary policy. In contrast, we focus on the shortterm goals of monetary policy. In addition, we provide empirical estimates of the impact that changes in reserve requirements are likely to have on volatility in the money market. Previous studies were largely theoretical and, therefore, could only show that the impact of a change in policy depended on various unknown parameters of a particular model.